Exploring the Potential Antidepressant Mechanisms of TNFα Antagonists - Brymer, Kyle J.; Romay-Tallon, Raquel; Allen, Josh; Caruncho, Hector J.; Kalynchuk, Lisa E. (Frontiers in Neuroscience, 2019)
Human and animal studies suggest an intriguing relationship between the immune system and the development of depression. Peripherally produced cytokines enter the brain through activation of microglia or through a system of lymphatic vessels. Once inside the brain, prolonged elevation of pro-inflammatory cytokines (e.g., TNF-α) can instigate a cascade of events including decreases in markers of synaptic plasticity and increases in neurodegenerative events. This is exemplified by preclinical studies, which show that peripheral administration of pro-inflammatory cytokines can elicit depression-like behavior. Importantly, this depression-like behavior can be ameliorated by anti-cytokine therapies. Work in our lab suggests that TNF-α is particularly important for the development of a depressive phenotype and that TNF-α antagonists might have promise as novel antidepressant drugs. Future research should examine rates of inflammation at baseline in depressed patients and whether anti-inflammatory agents could be included as part of the treatment regimen for depressive disorders.